2010
DOI: 10.1587/transinf.e93.d.233
|View full text |Cite
|
Sign up to set email alerts
|

Query-Number Preserving Reductions and Linear Lower Bounds for Testing

Abstract: SUMMARYIn this paper, we study lower bounds on the query complexity of testing algorithms for various problems. Given an oracle that returns information of an input object, a testing algorithm distinguishes the case that the object has a given property P from the case that it has a large distance to having P with probability at least 2 3 . The query complexity of an algorithm is measured by the number of accesses to the oracle. We introduce two reductions that preserve the query complexity. One is derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…We study graphs that are far from being Hamiltonian. Hamiltonicity is known to be hard for property testing Yoshida and Ito (2010); Goldreich (2020). However this is shown via a randomised construction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We study graphs that are far from being Hamiltonian. Hamiltonicity is known to be hard for property testing Yoshida and Ito (2010); Goldreich (2020). However this is shown via a randomised construction.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand there are some properties whose query complexity is sublinear but not constant, e. g. bipartiteness Ron (2002, 1999). Furthermore, there are some properties for which no tester with sublinear query complexity exists, e. g. Hamiltonicity Yoshida and Ito (2010); Goldreich (2020), 3-colourability Bogdanov et al (2002, independent set size Goldreich (2020). Note that for any computable property there is a linear query complexity property tester, i. e. the tester, which accesses the entire graph and then uses any exact algorithm for the property, as we do not bound the running time of a property tester.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bogdanov, Obata, and Trevisan [10] showed the first Ω(n) lower bound for Boundeddegree graph 3-colorability, and furthermore for Vertex Cover, Max Cut, Max 2SAT, Max E3SAT † , and Max E3LIN-2 † † , where all the above problems are in the boundeddegree model, by introducing a reduction method. Later, Yoshida and Ito [39] showed that 3-edge-colorability, Directed/undirected Hamiltonian path/cycle, 3-dimensional matching, and Schaefer-type generalized 3SAT, all in the bounded-degree model, also have the same (linear) lower bounds by introducing some new reduction methods.…”
mentioning
confidence: 99%